Motivasi Belajar Siswa melalui Media Snake and Ladder Game Berbasis Etnomatematika Palembang pada Pembelajaran Matematika - Luvi Antari; Syaifuddin; Ummu Na'imah; Amrina Rizta; Rohman (FKIP Universitas PGRI Palembang, 2026)
This study aims to describe the level of learning motivation among MTs students toward the use of Snake and Ladder Game media based on Palembang ethnomathematics in mathematics learning for Grade VIIA. This study employed a quantitative descriptive approach involving 20 MTs students in December 2025. The research instrument was a five-point Likert scale questionnaire consisting of 25 statement items, which had been tested for validity using Pearson correlation and for reliability using Cronbach’s Alpha, with a reliability coefficient of 0.82. The data were analyzed using descriptive statistics with the assistance of SPSS. The results showed a total score of 1650 out of a maximum score of 2000, with a percentage of 82.5%, which falls into the very high category. The dominant indicators of learning motivation included learning interest at 85%, self-confidence at 82%, curiosity at 80%, appreciation at 78%, and learning goals at 75%. These findings indicate that the use of Snake and Ladder Game media based on Palembang ethnomathematics, which integrates the geometry of songket motifs, the arithmetic context of the 16 Ilir market, and the cultural context of the Ampera Bridge, shows potential to support interactive, contextual, and enjoyable mathematics learning. The findings also suggest that this media can serve as a learning alternative that is relevant to students’ characteristics, particularly in supporting learning motivation through local cultural contexts. The implication of this study is that teachers may adapt ethnomathematics-based game media as one of the contextual and culturally integrated strategies in mathematics learning. Future studies are recommended to employ a quasi-experimental design or a mixed-methods approach to examine the effect of the media on students’ motivation and learning outcomes in greater depth.